cloudalicious: folksonomy over time - Russell, Terrell (International Conference on Digital Libraries: Proceedings of the 6th ACM/IEEE-CS joint conference on Digital libraries; 11-15 June 2006, 2006)
Cloudalicious is an online visualization tool that has been designed to give insight into how Òtag cloudsÓ, or folksonomies, develop over time. A folksonomy is an organic system of text labels attributed to an object by the users of that object. The most common object so far to be the subject of this tagging has been the online bookmark. Stabilization of a URL's tag cloud over time is the clearest result of this type of visualization. Any diagonal movement on the graphs, indicative of a change in the tags being used to describe a URL, should garner further discussion.